2003
DOI: 10.1176/appi.ajp.160.1.83
|View full text |Cite
|
Sign up to set email alerts
|

High-Dimensional Mapping of the Hippocampus in Depression

Abstract: Patients with major depression may have structural abnormalities of the hippocampus that can be detected by analysis of hippocampal shape but not volume. A specific defect in the subiculum could have widespread effects throughout neurocircuits that appear to be abnormal in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
1
8

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(125 citation statements)
references
References 38 publications
8
108
1
8
Order By: Relevance
“…MacQueen and colleagues 40 found a significant logarithmic association and Sheline and colleagues 41 a significant linear association between hippocampus volume and total illness duration. However, other studies 35,38,42 did not find any association between clinical variables and decreased volume in the hippocampus or amygdala. For the OFC, in agreement with our study, Bremner and colleagues 22 and Lacerda and colleagues 28 reported no significant association between OFC volume decrease and clinical variables.…”
Section: Discussionmentioning
confidence: 73%
“…MacQueen and colleagues 40 found a significant logarithmic association and Sheline and colleagues 41 a significant linear association between hippocampus volume and total illness duration. However, other studies 35,38,42 did not find any association between clinical variables and decreased volume in the hippocampus or amygdala. For the OFC, in agreement with our study, Bremner and colleagues 22 and Lacerda and colleagues 28 reported no significant association between OFC volume decrease and clinical variables.…”
Section: Discussionmentioning
confidence: 73%
“…Shape analysis has been shown to be complementary to volumetry in discriminating between normal and neuropsychiatric conditions (34,35). Recently, we used shape analysis to characterize basal ganglia structure in subjects with schizophrenia (36).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…In subjects with MDD or a history of MDD, MRI studies demonstrate reduced volume of the hippocampus (Bremner et al 2000;Frodl et al 2002;MacQueen et al 2003;Mervaala et al 2000;Shah et al 1998;Sheline et al 1996Sheline et al , 1999Steffens et al 2000; but not in Posener et al 2003;Rusch et al 2001;Vakili et al 2000). It appears that hippocampal atrophy is preferentially seen in older, recurrently depressed subjects or subjects who are refractory to antidepressant medications.…”
mentioning
confidence: 97%